Eksistensi Sistem Perkawinan Exogami Masyarakat Adat Batak Toba di Kota Jakarta - Putra, Theo Arunggi; Mulya, Musa Alam (Neolectura, 2025)
The purpose of this paper is to describe the development of the Batak Toba traditional marriage system in Jakarta, as well as its process of adaptation and transformation in relation to Law No. 1 of 1974. This research employs a socio-legal approach, which examines law not only as written norms (law in books), but also as a social reality that lives and evolves within society (law in action). Based on the discussion above, the following conclusions can be drawn: first, the Batak Toba traditional marriage system in Jakarta has undergone dynamic development, reflecting the community's efforts to preserve their cultural identity while adapting to the social, legal, and economic realities of urban life, particularly in Jakarta. This illustrates that customary law is not a static entity, but rather adaptive to the changing times. Second, the adaptation and transformation of the Batak Toba marriage system within the context of Law No. 1 of 1974 is a dynamic and dialogical process. On one hand, state law demands certainty and equality; on the other hand, customary law serves to preserve identity and social solidarity.